Drug particle size influence on enteric beads produced by a droplet extrusion/precipitation method - Cerdeira, AM (2015)
The influence of drug particle size on the production of enteric beads by a polymer precipitation technique was investigated. Drug particle dimensions are known to play an important role in most microencapsulation techniques. Bead morphology was greatly influenced bq drug particle size, and spherical shaped beads could only be obtained after size reduction of nimesulide crystals. This is confirmed by the angle of repose measurements, which show a significant decrease in theta values when beads are formulated with smaller drug particles. Furthermore, results show that drug encapsulation efficiency and in vitro drug release rates are also greatly dependent on both drug particle size and drug/ polymer ratio in the initial suspension. Preparations containing 10.2 mu m drug particles show a two-fold increase in the release rates when compared tc, those prepared with 40 mu m particles.